COACHING CLINIC BOLA VOLI BAGI PEMAIN BOLA VOLI DESA/KEC. CIKAUM BARAT, KAB. SUBANG - Tirto Apriyanto; Muhamad lham; Agus Salim (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2022)
Abstract The purpose of this service activity is to help solve partner problems, namely; The problem of overcoming social conflicts that often occur in West Cikaum District, volleyball coaching in the village as a form of coaching the potential is quite large in West Cikaum village, lack of knowledge and understanding of volleyball athletes in the village in improving the skills of volleyball. Assistance in solving partner problems is carried out through a systematic, structured, and measurable process of tracing the potential of regional sports. Coaching Clinic volleyball is one of the short training programs that aims to improve the knowledge and skills of coaching, teaching volleyball. Assistance in solving partner problems is carried out through a systematic, structured, and measurable process of tracing the potential of regional sports. Coaching Clinic volleyball is one of the short training programs that aims to improve the knowledge and skills of coaching, teaching volleyball. Service activities will be held on May 11-13, 2022, in the form of lectures on volleyball coaching and practice, discussions and questions and answers, as well as friendly matches with students involved in this activity. The subject of the participants was volleyball player Oskar as many as 20 players. Coaching Clinic on this occasion is so that teenagers in West Cikaum village can improve their knowledge and skills in playing volleyball, especially in the aspects of technique, physique, and regulations. The results of this Coaching Clinic program also obtained a participant satisfaction score of 87.5% which means that the level of satisfaction is quite high. Abstrak Tujuan kegiatan pengabdian ini adalah membantu menyelesaikan permasalahan mitra yaitu; Permasalahan mengatasi konflik sosial yang sering terjadi di Kecamatan Cikaum Barat, pembinaan olahraga bola voli di desa sebagai bentuk pembinaan potensi cukup besar di desa Cikaum Barat, kurangnya pengetahuan dan pemahaman atlet bola voli di desa dalam meningkatkan kemampuan keterampilan cabang olahraga bola voli. Bantuan penyelasaian permasalahan mitra dilakukan melalui proses penelusuran potensi olahraga daerah secara sistematis, terstruktur, dan terukur. Coaching Clinic bola voli merupakan salah satu program pelatihan singkat yang bertujuan untuk meningkatkan pengetahuan dan keterampilan melatih, mengajar voli. Kegiatan pengabdian dilaksanakan pada tanggal 11- 13 Mei 2022, berupa kegiatan ceramah tentang pembinaan dan latihan bola voli, diskusi dan tanya jawab, serta pertandingan persahabatan dengan mahasiswa yang terlibat dalam kegiatan ini. Subjek peserta adalah pemain bola voli Oskar sebanyak 20 pemain. Coaching Clinic pada kesempatan ini adalah agar remaja di desa Cikaum Barat dapat meningkatkan pengetahuan dan keterampilan bermain bola voli terutama dalam aspek teknik, fisik, dan peraturannya. Hasil dari program Coaching Clinic ini juga diperoleh nilai kepuasan peserta sebesar 87,5% yang berarti tingkat kepuasan cukup tinggi.